Model Pemberdayaan Masyarakat Dalam Pencegahan Cikungunya di Desa Ledug Kecamatan Kembaran - Yuliarti, Yuliarti; Kusuma Aryani , Ine; Wijarnako Kertopati , Beny (Universitas Pahlawan Tuanku Tambusai, 2023)
Chikungunya fever is an infectious disease caused by alphavirus which is spread by the bite of mosquitoes of the Aedes aegypti species. In Banyumas Regency, recently the incidence of Chikungunya fever has increased again. At least hundreds of residents in a number of villages have contracted Chikungunya fever. The aim of this activity is for the community to have a good understanding of chikungunya (causes, management, treatment), to be able to independently carry out preventive measures against chikungunya, and to be able to take initial steps to deal with chikungunya incidents within the family before the patient is taken to a service location. health. The activities that will be carried out include cognitive aspects with the aim of understanding mastery of the material by working on practice questions as in the attachment, carried out before and after the activities are carried out (pre and post test), while in the affective and psychomotor aspects group discussions will be carried out using the FGD model. (focus group discussion) and emergency simulation activities for cikungnya patients. Meanwhile, monitoring the role of cadres in empowering the community to prevent cikungunya outbreaks is carried out in the form of evaluating the results of jumantik (larvat monitoring officers) activities carried out in each RW. The target of the activity is the community, especially posyandu cadre mothers and the PKK mobilization team in Ledug Village, Kembaran District. The activity was carried out on Sunday, April 19 2022, attended by 25 posyandu cadres and 15 Village PKK mobilization teams, located at the Ledug Village hall. The activities carried out covered 3 main topics: First, education about chikungunya. Second, delivery of material on eradicating mosquito nests (PSN) and larva monitoring (Jumantik), and third, delivery of material on emergency nursing for chikungunya patients, as well as simulating the emergency situation of dengue fever patients before being referred to the hospital. The next stage of activities is aimed at the village PKK mobilization team to become extension officers. The activity schedule adjusts to the regular meeting schedule. In this second stage, the implementing team for implementing science and technology for the community only carries out monitoring and evaluation during activities in each RT. The results of the evaluation of activities in the second stage, seen from the larva monitoring activities (jumantik) by members of the PKK driving team, are expected to continue, as an effort to prevent the cikungunya outbreak. In conclusion, the implementation of community empowerment model activities in efforts to prevent chikungunya shows positive results, and cadres are the spearhead of driving community participation in PSN activities (eradicating mosquito nests) especially in larva monitoring (jumantik) activities